Program Penguatan Ilmu Falak Club Astronomi Santri Assalam (CASA) (Studi Kasus di Pondok Pesantren Modern Islam (PPMI) Assalaam Surakarta) - Nur Fadhilah Al-Karimah; Mudhofir Abdullah; Imam Mujahid (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Falak science cannot be separated from the world of pesantren. Nowadays falak science is starting to be less popular in the world of pesantren, it is less populist with other sciences such as nahwu, neuroscience, tahfidz al-Qur'an or hadith, besides that falak is also considered a difficult science because it is identical to mathematics and calculation formulas. However, based on observations made by the author, it turns out that there are still Islamic boarding schools, especially the Islamic Modern Islamic Boarding School (PPMI) Assalaam Surakarta, developing science called CASA (Students Assalam Astronomy Club) with the aim of giving birth to golden generations who are experts in the field of mastering Islamic science, and also become experts in technology and experts in science and astronomy. The type of research used is a type of qualitative research with a field approach (field Reseacrh), where the author analyzes data sources obtained from the field. The data collection methods used are observation, documentation and interview methods. The primary sources are observations and interviews. After the data was collected, the author conducted an analysis using a descriptive analysis method, which describes the strengthening of the astronomy club of the Islamic boarding school and the conditions for the development of science in the Islamic boarding school. The results of this study show that CASA is now growing and has a prestigious place among the community of astrologers. CASA collaborates with Bosscha Observatory in Lembang, Bandung, West Java and builds international networks with Astronomers Without Borders, Astronomy Clubs, Moonsighting Committee Worldwide, to the National Aeronautics and Space Administration (NASA) owned by the United States government. CASA was certified by NASA for successfully observing and documenting the transit of Venus in June 2012. This transit or eclipse of Venus is a rare natural phenomenon that occurs once every 105 years when the planet Venus passes right on the surface of the sun.